THE CONTRIBUTION OF SMALL AND MEDIUM-SIZED ENTERPRISES IN THE ALGERIAN ECONOMY: AN ENTROPY INDEX APPROACH - Khaled Khellil; Kamilia Loucif (Acta Economica)
The role of small and medium enterprises in the economic development of nations cannot be overstated. These businesses, ranging from small family-owned bakeries to medium-sized manufacturing plants, play a vital role in job creation, innovation, and overall economic growth. Numerous studies have established the crucial significance of SMEs to economic success and the development of regions. Our research aims to investigate the extent to which SMEs in Algeria contribute to the country’s economic development and diversification. Considering the economic status of Algeria as a developing nation heavily reliant on oil revenues, it presents a unique case for study. To achieve our research objectives, over 120 official government reports published between 2001 and 2022 are analysed. Descriptive data analysis was conducted, and the Entropy index was calculated to address the problematics and verify the hypotheses. The results reveal that SMEs in Algeria make considerable contributions to employment rates and GDP values. However, their numbers in export operations are very low. The study found that SMEs in Algeria are potent locally, but their performance in global markets is very poor.